FACTORS INFLUENCING CAREER CHOICE OF FINAL YEAR BUSINESS STUDENTS IN POLYTECHNIC UNGKU OMAR - Jaafar, Siti Salwa; Omar, Mahyudin; Abdul Aziz, Zaidah (International Business Education Journal, 2019)
The transition into the working world is a major life change for many college or university students, during which they face the complex demands of economy, a challenging, highly competitive job market, as well as increasingly diverse population and work force. In light of the changing nature of work, it is important to understand the career choice and exploration and how they relate to the multidimensional conceptualization of careers in the 21st century. This paper analysed the influences of various factors on the career choice of final year business students in Polytechnic Ungku Omar (PUO), Ipoh, Perak. This paper also examined the importance of family/individual and non-family/external influence, career goal and success and role of values in making career choices among these students. From the data analysis, it appeared that family and non-family factors do have significant influence on the students’ decisions of their choice of career. Another factor which was also an important determinant that influenced career “choice” of students was the cultural dimension of individualism-collectivism. However data analysis conducted revealed that students regarded both individualism and collectivism as equally important factors in determining their career choices.